Revitalization of Marriage Guidance Curriculum: Strengthening Religious Moderation for Family Resilience in Jambi Province - Rahmawati (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This paper highlights the critical gap between the high volume of marriage services in the Religious Affairs Office (KUA) of Jambi Province and the lack of substantive intervention regarding radicalism prevention in the Marriage Guidance (Bimwin) curriculum. Despite serving over 21,590 marriages in 2024, the current curriculum remains administrative-heavy and lacks adaptive content on religious moderation, leaving new families vulnerable to ideological infiltration. The study employs a qualitative policy analysis approach using the USG (Urgency, Seriousness, Growth) method to determine priority issues and the Fishbone diagram to identify root causes. Furthermore, alternative policy solutions are evaluated using William N. Dunn’s criteria: effectiveness, efficiency, adequacy, equity, and responsiveness. The analysis reveals that the absence of binding regulations and standardized curriculum integration is the core problem. The results indicate that issuing a Circular Letter (Surat Edaran) is the most viable policy alternative compared to pilot projects or forming special teams. Consequently, this study recommends that the Regional Office of the Ministry of Religious Affairs in Jambi Province immediately issue a Circular Letter mandating the integration of religious moderation and anti-radicalism materials into the Bimwin curriculum. This policy is expected to transform KUA from a mere administrative body into a proactive agent for strengthening national resilience through the family unit.